Knowledge and practices toward COVID-19 among healthcare students: A cross-sectional study at the University of Zambia - Mudenda, Steward; Ngalande, Nelly; Mukosha, Moses; Hikaambo, Christabel Nang'andu; Daka, Victor; Matafwali, Scott Kaba; Banda, Michelo; Mfune, Ruth Lindizyani; Mayoka, Godfrey; Witika, Bwalya Angel (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic led to the disruption of physical classes for university students globally, as large gatherings fuelled the transmission of the virus. In the efforts to mitigate its transmission and return to normality, prevention measures, including vaccination, have been encouraged. Materials and methods: This questionnaire-based cross-sectional study was carried out from August 2021 to October 2021 among healthcare students (pharmacy, physiotherapy, nursing, biomedical, medicine, and radiography). We used a previously validated questionnaire to measure knowledge and practice. The predictors of knowledge and practices were assessed using logistic regression. Statistical analysis was conducted using Stata/BE version 17.0. Results: Of the 478 respondents, 243(50.8%) were females. A larger proportion, 175(36.6%) were in Pharmacy training, and 156 (32.6%) were in their fifth year of study. The overall mean knowledge score of the participants was 87.9(SD=16.1), being higher at 89.6(SD=14.3) among medical students and the lowest at 86.7(SD=17.1) among Pharmacy students, although this was statistically non-significant (p=0.488). The overall mean practice score was 60.0(SD=24.7), being significantly higher at 63.5(23.4) among nursing, physiotherapy and environmental students compared to other students (p=0.048). In multivariable analysis, the participant training program was non-significantly associated with knowledge and practice towards COVID-19. However, increased age (AOR=1.09, 95% CI: 1.01-1.117) and residing in urban areas (AOR=1.79, 95% CI: 1.07-3.01) than in rural areas were associated with higher odds of good practice toward COVID-19. Conclusion: The healthcare students generally showed good knowledge levels and poor practices toward COVID-19. Further, there was no evidence of a difference in knowledge of COVID-19 among healthcare students. These findings suggest the need for implementation strategies to be centred on improving the practices among the students. In addition, future studies should assess the attitudes towards COVID-19 among healthcare students.